Halloysite-Nanotube-Mediated High-Flux γ-Al2O3 Ultrafiltration Membranes for Semiconductor Wastewater Treatment - Shining Geng; Dazhi Chen; Zhenghua Guo; Qian Li; Manyu Wen; Jiahui Wang; Kaidi Guo; Jing Wang; Yu Wang; Liang Yu; Xinglong Li; Xiaohu Li (Membranes)
The wastewater from Chemical Mechanical Polishing (CMP) generated in the semiconductor industry contains a significant concentration of suspended particles and necessitates rigorous treatment to meet environmental standards. Ceramic ultrafiltration membranes offer significant advantages in treating such high-solid wastewater, including a high separation efficiency, environmental friendliness, and straightforward cleaning and maintenance. However, the preparation of high-precision ceramic ultrafiltration membranes with a smaller pore size (usually <20 nm) is very complicated, requiring the repeated construction of transition layers, which not only increases the time and economic costs of manufacturing but also leads to an elevated transport resistance. In this work, halloysite nanotubes (HNTs), characterized by their high aspect ratio and lumen structure, were utilized to create a high-porosity transition layer using a spray-coating technique, onto which a γ-Al2O3 ultrafiltration selective layer was subsequently coated. Compared to the conventional α-Al2O3 transition multilayers, the HNTs-derived transition layer not only had an improved porosity but also had a reduced pore size. As such, this strategy tended to simplify the preparation process for the ceramic membranes while reducing the transport resistance. The resulting high-flux γ-Al2O3 ultrafiltration membranes were used for the high-efficiency treatment of CMP wastewater, and the fouling behaviors were investigated. As expected, the HNTs-mediated γ-Al2O3 ultrafiltration membranes exhibited excellent water flux (126 LMH) and high rejection (99.4%) of inorganic particles in different solvent systems. In addition, such membranes demonstrated good operation stability and regeneration performance, showing promise for their application in the high-efficiency treatment of CMP wastewater in the semiconductor industry.